Law Amending and Supplementing a number of articles of the Law on Complaints and Denunciations - The National Assembly (2004)
This Law amends and supplements a number of articles of the Law on Complaints and Denunciations, which was passed on December 2, 1998 by the National Assembly of the Socialist Republic of Vietnam